What’s New? Gestures Accompany Inferable Rather Than Brand-New Referents in Discourse - Debreslioska, Sandra; Gullberg, Marianne (Frontiers in Psychology, 2020)
The literature on bimodal discourse reference has shown that gestures are sensitive to referents’ information status in discourse. Gestures occur more often with new referents/first mentions than with given referents/subsequent mentions. However, because not all new entities at first mention occur with gestures, the current study examines whether gestures are sensitive to a difference in information status between brand-new and inferable entities, and variation in nominal definiteness. Unexpectedly, the results show that gestures are more frequent with inferable referents (hearer-new but discourse-old) than with brand-new referents (hearer- and discourse-new). The findings reveal new aspects of the relationship between gestures and speech in discourse, specifically suggesting a complementary (disambiguating) function for gestures in the context of first mentioned discourse entities. The results thus highlight the multi-functionality of gestures in relation to speech.